ANALYSISS IMPLEMENTATION OF THE FAMILY HOPE PROGRAM (PKH) IN PARANGJORO VILLAGE - JFX Susanto Soekiman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this research is to identify the implementation of the distribution of funds for the family hope program. The research method is descriptive qualitative and the analysis techniques of Miles, Huberman and Saldana, this study will describe the stages of determining the participants who are declared deserving of poverty and also the obstacles in their implementation. Poverty is an important problem for Indonesia until now, so that it is the government's responsibility in the context of community welfare. Therefore, the Indonesian government must allocate a lot of expenditure for these poverty reduction programs and activities. One of the programs that has been carried out by the Indonesian government is the Family Hope Program (PKH). PKH is a conditional program whose target is to improve public welfare in the health and education sectors. Parangjoro Village is one of the villages in Indonesia that has received PKH program assistance. The results of the study revealed that the determination of PKH participants was based on existing data in the Integrated Social Welfare Data System (DTKS), but it was still carried out to check the truth of the participant's condition until it was re-verified by the Ministry of Social Affairs. Meanwhile, the obstacle in the implementation is still difficult to gather all the participants together every month for checking and coaching. but it was still carried out to check the truth of the participant's condition until it was re-verified by the Ministry of Social Affairs. Meanwhile, the obstacle in the implementation is still difficult to gather all the participants together every month for checking and coaching. but it was still carried out to check the truth of the participant's condition until it was re-verified by the Ministry of Social Affairs. Meanwhile, the obstacle in the implementation is still difficult to gather all the participants together every month for checking and coaching. Kkeywords: Poverty; Implementation Analysis; Family Hope Program